Endocrinology and Autoimmune Diabetes - Majid Abd Ulameer Alhumairi, Rasha; I K Aljuboori, Shaymaa; Aso Taher, Tara; Tariq Sabaar, Zeena (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Therapists within the constantly evolving area of endocrinology, including diabetes treatment in especially, have to rapidly incorporate novel knowledge into their daily practice. Endocrinology is a field of medical or physiology that examines the endocrine system, including its hormonal substances, or disorders. It is structured in an interesting, individualized manner. A frequent endocrine condition that impacts the amount of sugar in the blood called diabetes. There are some linked facts regarding endocrinology as well as diabetes: this style gives readers an additional accessible or targeted method to quickly answer particular medical issues by listing them. This extensive written content, which encompasses the most prevalent medical challenges in endocrinology or diabetes, has been created by a famous, worldwide panel of specialists. Endocrinologists, diabetic specialists, internal health medical professionals, general doctors, fellows, or resident would all find it very interesting.